Realizar un estudio de factibilidad para la creación de una empresa productora de café molido para el consumo en el Quindío (2013)
The project's feasibility study for the implementation of a processor and marketer of roasted and ground coffee in the department of Quindio. This project would provide the possibility to Quindio people to purchase products made in 100% high quality quindio. Company is to install a coffee roaster and marketer, to meet the needs of the mass market, this market is particularly attractive because of the high volume of purchases and the few technical requirements of the product required by the customer, making the production and marketing processes more efficient and therefore cheaper, to reflect these aspects in a high yield.